Optimizing Lupus Care: Early Intervention to Prevent Organ Damage - Jose Alfredo Gómez Puerta (Journal of Clinical Rheumatology and Immunology)
Dr. Jose Alfredo Gómez Puerta’s upcoming lecture at ICCR 2024 will delve into the critical issue of organ damage in patients with systemic lupus erythematosus (SLE), highlighting the limitations of current standard care practices. He will begin by discussing the risks associated with persistent disease activity and the traditional use of high-dose steroids, which often lead to significant organ damage over time. Dr. Gómez Puerta will then present a paradigm shift in SLE treatment as recommended by the European League Against Rheumatism (EULAR) 2023 guidelines and share the clinical impact brought by the new recommendations. The guidelines advocate for reducing chronic steroid dosage and emphasize early intervention with biologic therapies to minimize the risk of long-term organ damage. The lecture will feature new evidence supporting the benefits of early biologic intervention in managing SLE. Dr. Gómez Puerta will present data from recent studies demonstrating improved patient outcomes, including reduced disease flares and lower drug-related toxicities. These findings underscore the importance of integrating biologic therapies earlier in the treatment regimen to achieve better disease control and enhance long-term patient health. In addition to discussing empirical data, Dr. Gómez Puerta will share real-world cases illustrating the positive impacts of early biologic intervention. These case studies will provide practical insights into how this approach can be effectively implemented in clinical practice, showcasing its potential to alter the natural course of SLE by delaying organ damage and improving the quality of life for patients. Finally, the lecture will emphasize the need to optimize SLE management beyond short-term symptom relief. Dr. Gómez Puerta will advocate for strategies focused on long-term disease management, aiming to reduce flares, mitigate drug toxicities, and ultimately prevent organ damage. This comprehensive approach is crucial for altering the disease’s trajectory and achieving disease modification for SLE patients.